A pan-cancer analysis of synonymous mutations - Sharma, Yogita; Miladi, Milad; Dukare, Sandeep; Boulay, Karine; Caudron-Herger, Maïwen; Groß, Matthias; Backofen, Rolf; Diederichs, Sven (Nature Communications, 2019)
Synonymous mutations do not alter amino acid sequence but may exert oncogenic effects in other ways. Here, the authors present a catalogue of synonymous mutations in cancer and characterise their properties.